A program for self-concept enhancement: An experimental pilot study - De Sam Lazaro, Ma. Consilia (Animo Repository, 1980)
This experimental study determined the effectivity of a proposed Self-Concept Enhancement Program to facilitate the enhancement of self-concept among randomly selected students of the fourth year level of the Ramon Magsaysay High School, Espana, Manila. A total of 22 randomly selected fourth year students having low self-concepts, 11 for the experimental group and 11 for the control constituted the sample. The randomized pretest and posttest control group design was used with only the experimental group being exposed to the treatment variable which was a program designed to enhance the self-concepts of the participants. Sandler's A tests were made to determine whether there were significant gains in over-all self-concepts and in the eight subscale dimensions of the Tennessee Self-Concept Scale in both groups. The findings among the experimental group revealed significant gains in overall self-concept and in two dimensions of the subscales, namely in R2. Self-Satisfaction and E. Social Self. Among the control group findings show significant gains in E. Social Self. Apart from these significant gains, there were appreciable though not significant gains among the experimental group in three other dimensions of the Tennessee Self-Concept (TSC) Subscales namely R1. Self-Identity, A. Physical Self and D. Family Self. The control group showed a positive though not significant change in R3. Self-Behavior. Upon weighing and analyzing the findings, the researcher is led to conclude that the Self-Concept Enhancement Program did, in some measure, effect a significant increase in overall self-concept as well as in self-satisfaction among the experimental group. In fine, the students in the experimental group experienced a positive change in their feelings about themselves and in their total self-concept. However, because of the limitations of sample size, the above statements were only tentative and suggestive of the need for additional research.